SYSTEMATIC LITERATURE REVIEW: INTEGRASI KONSEP TEOREMA PYTHAGORAS DALAM KEGIATAN BELAJAR BERSAMA ALAM - Mukhlesi Yeni, Ety; Nurhayati; Putri Salehha, Osey (Universitas Pasifik Morotai, 2025)
Education is an essential process aimed at developing the individual’s potential holistically, encompassing intellectual, emotional, and social aspects. The School of Nature, as an innovative approach to education, uses nature as the primary learning medium, offering relevant contextual experiences for students. SMP Sekolah Alam Bireuen (SABIR) implements the